TAHLILUL AKHTHA’ FI MAHAROTI AL-KALAM BI AL-LUGHAH AL-ARABIYAH LITHULLABI MA’HADI SIRAJU AL-THALIBIN AL-ISLAMI - Kurniawati, Ela; Ni'mah, Mamluatun; Sofa, Ainur Rofiq (El-Tsaqafah : Jurnal Jurusan PBA, 2024)
This research is motivated by the issues related to the low ability of students in pronouncing letters, words, or sentences in Arabic, especially for beginner learners, to prevent future errors that may hinder the learning process. This study aims to analyze students' errors in reading Arabic texts from a phonological perspective. It is a qualitative research with a descriptive research design. The results of this research are as follows. Firstly, the phonological error forms in Arabic speaking skills among students of the Siraaj Al-Thalibin Islamic boarding school include errors in throat consonant groups (?????) and tongue groups (??????); vowel errors such as vowel deletion, vowel substitution, and long-short vowel errors; diphthong errors; double consonant errors (????); and assimilation errors (??). Secondly, the factors causing errors in Arabic language speaking skills include linguistic and non-linguistic factors. Non-linguistic factors such as low interest and motivation in language learning, and lack of application of the Arabic language.